Dietary calcium and phosphorus level for sows - Maxson, P.F. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
The past decade has seen increased emphasis upon sow research. With the strong pressure toward increased sow productivity, there continues to be a need for evaluation of sow nutrient requirements. One area that has received much attention is the calcium (Ca) and phosphorus (P) needs of gestating and lactating swine. Research has increased our knowledge of Ca and P for reproducing swine but there is still a great deal to be ascertained regarding the mineral requirements of the sow. There continues to be concern over the high incidences of leg soundness and posterior paralysis problems in reproducing sows. The most frequent reason given for this situation is insufficient dietary levels of either Ca, P, and (or) vitamin D for reproductive purposes.
Keywords: Swine; Calcium; Phosphorus; Sows